STRENGTH PROPERTIES OF TEN SOUTH INDIAN CANES - K. M. Bhat; P. K Thulasidas; C.P. Mohamed, (Journal of Tropical Forest Science (JTFS), 1992)
Selected mechanical properties such as static bending, tensile and compression strengths (parallel to grain) of ten South Indian rattan species representing large, medium and small diameter categories were determined. Based on the mean strength values, these species may be classified into strong to very strong (Class I - MOR and UTS > 70 Nmm-2, moderately strong (Class II - MOR and UTS 45- 70 Nmm-2) and weak (Class III -MOR and UTS < 45 Nmm-2) rattans. The two strongest rattans, viz Calamus nagbettai and C. gamblei come under the Class I while the weakest rattans, C. lacciferus and C. metzianus, which are commercially less important species, fall under the Class III. Majority of the species come under Class II. Generally, the strength values of Indian rattans are comparable to those of Southeast Asian rattans. Within the stem, strength decreases from the periphery to the centre and from the base to the top correlating with fibre proportion and specific gravity. The most important factors that influence strength properties are species, age, stem position, fibre (sclerenchyma) proportion, specific gravity and moisture content.